Dynamics of Corruption Eradication in Saudi Arabia - Ilhami, Muhammad Fadly; Muttaqin, Mohammad Izdiyan (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The eradication of corruption has become an important issue in many countries, including Saudi Arabia and Indonesia. Saudi Arabia has implemented rapid and stringent methods to combat corruption, including the establishment of anti-corruption commissions and the arrest of princes and ministers suspected of involvement. This research method utilizes literature review and opinion survey. However, the application of Saudi Arabia's methods in Indonesia faces challenges and contextual differences that need to be considered, including legal context, cultural and local values, transparency and accountability, education and public awareness, and structural reforms. The application of methods from other countries should be done carefully, taking into account local conditions to ensure effectiveness and sustainability in anti-corruption efforts. The process of combating corruption should remain based on the principles of law, respecting human rights, and involving community participation in efforts to achieve clean and accountable governance in Indonesia.